A study of the impact of the resource thermal power plants with ‘de-industrialised design’ on the NIMBY effect - Li Qiuyan; Tian Ruifeng (E3S Web of Conferences)
The construction of the resource thermal power plant has negative impacts on the surrounding residents and it causes the NIMBY effect. The “de-industrialized” design can alleviate the NIMBY effect of the power plant to a certain extent. This paper quantifies the degree of impact of resource thermal power plant with“de-industrialization design” to the NIMBY effect from the perspective of housing prices. It takes Shenzhen Eastern Energy Eco-Park as example to analyze the changes in price of the Second-hand Properties around Power Plants by Hedonic-Price Models and Kriging Interpolations. The results of the study show that the resource thermal power plants with ‘de-industrialised design’ can effectively mitigate the NIMBY effect. Within a certain range, the magnitude of the impact decreases with distance. So it is suggested that the construction of the resource thermal power plant should be adapted to the local conditions, and the application of the “de-industrialization” design should be used to improve the acceptance of the residents of the plan to create a good human environment.